Cognitive Analysis of nafsat al masdur zeydari nasavi Relying on three concepts frequently(heart, Sorrow, World) - لیلا حر; محمدعلی خزانه دارلو (مطالعات زبانی و بلاغی)
This paper after introducing a cognitive approach to metaphor, intends to investigate metaphoric concepts which are formed in Nafsat al Masdour of Mohammad  Zeydari. The aim of this study, Identifying  Zeydari’s mental structure relative to the events which he faced in his life. Since the language is a tool to explore the structure of  the human cognitive system and conceptual metaphor represents the content function of conformity the areas of the source and destination And each metaphor is typically a reflective of mentality and vision of its creator, So the events written in this book and the abstract categories contained in it can be better understood simply by using tangible concepts and through sensory experience. The authors have responded to some questions by using descriptive methods and library studies in the frame work  of  Lakoff and Johnson’s theory like: What is the central metaphor of Nafsat al Masduor and which metaphorical concepts have the most frequency? and whether the frequency of abstract concepts used in this book are consistent with the mentality of  its author and  title of the book?The findings of this study, shows that  Zeydary  in Nafsat al masduor  along  with the title of his book has used the concept of "hearts and sorrow" with the most frequency and he also has used the adverbial conceptual metaphor in its structure. In other words, the sorrow which overflows from heart is appeared in the form of the container and packaging in concepts of heart and sadness.